2023
DOI: 10.1002/slct.202303959
|View full text |Cite
|
Sign up to set email alerts
|

Novel Catalysis Systems for the Synthesis of Covalent Organic Frameworks

Yifan Zhu,
Jiahui Zhang

Abstract: Covalent organic frameworks (COFs), an emerging class of crystalline polymers, are meticulously constructed through covalent bonds, resulting in well‐defined structures and crystalline characteristics. Precise control over their architecture, permeability, and functionality can be easily achieved simply via selection of precursor monomers. The tailored architecture and functionality make COFs versatile for various applications including gas storage, pollutant removal, catalysis, and energy storage. Efficient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Recent research has demonstrated that Lewis acids can effectively catalyze the synthesis of imine COFs with high crystallinity. By leveraging the analogous Lewis acidity found in 2D inorganic materials like hBN and TMDs, we postulated that these materials could function as both catalysts and inorganic building blocks for creating COF/inorganic hybrids, enabling the controlled growth of COFs on the surface of such 2D materials. Herein, we present a general synthetic method for a series of COF/inorganic 2D material hybrids, catalyzed by various inorganic 2D materials, including hBN, molybdenum disulfide (MoS 2 ), molybdenum diselenide (MoSe 2 ), and tungsten disulfide (WS 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that Lewis acids can effectively catalyze the synthesis of imine COFs with high crystallinity. By leveraging the analogous Lewis acidity found in 2D inorganic materials like hBN and TMDs, we postulated that these materials could function as both catalysts and inorganic building blocks for creating COF/inorganic hybrids, enabling the controlled growth of COFs on the surface of such 2D materials. Herein, we present a general synthetic method for a series of COF/inorganic 2D material hybrids, catalyzed by various inorganic 2D materials, including hBN, molybdenum disulfide (MoS 2 ), molybdenum diselenide (MoSe 2 ), and tungsten disulfide (WS 2 ).…”
Section: Introductionmentioning
confidence: 99%